Adapt engineering theory in universal design for developing countries: a literature review - Eusuf, Muhammad Abu; Mamun, Abdullah Al; Salleh, Md. Noor; Ibrahim, Mansor; Mohd. Din, Shamzani Affendy; Abdul Rahim, Asiah (KAED Universal Design Unit (KUDU), 2016)
The aim of this study is to develop universal design by the application of engineering design theory, principles and solutions to permit in parallel use of the physical elucidations with full satisfaction on the utmost possible extent, irrespective of influential areas such as various types of buildings; open spaces and park; indoor circulation facilities and courtyard; means of communication services, pedestrian, infrastructure design and services.